(untitled) (Proceedings of International Conference on Special Education, 2017)
Children with Down syndrome are generally weak in the acquisition of language and social skills. To help them cope with these difficulties, it is necessary to implement early interventions at preschool level focusing on these two skills. Parents’ and teachers’ expectations on these children play a key role in determining ways of nurturing the children. The discrepancy of expectations of the two microsystems may bring about impacts on the children’s acquisition of these two skills. This study aimed to investigate the expectations of parents and teachers on language and social skills in children with Down syndrome. This is a quantitative research using a cross-sectional survey research design. The samples consist of 43 children with Down syndrome from Johor Bahru and Kulai. The parent of each child and 6 teachers who work at the sampling sites were the respondents of this study who answered the set of questionnaires on expectation for each Down syndrome child. The findings of the study showed that expectations of parents on children with Down syndrome with regard to language skills are moderate to high and exceptionally high for social skills. Responses from teachers showed varied expectations from low to high for language skills in these children. While for social skills, their expectations are generally moderate to high. There is a weak but not significant positive relationship found between the expectations of parents and teachers on both language and social skills in children with Down syndrome. This shows that the level of agreement between parents’ and teachers’ expectations are very low. These results implied that teachers and parents should meet and discuss their expectations so that a mutually agreeable specific action plan could be developed to promote effective learning on language and social skills for the child.